Choice of postpartum contraception and its socio-demographic and cultural determinants - Bangal, Vidyadhar B.; Thitame, Sunil; Somasundaram, K. V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Postpartum contraception is essential for avoidance of unwanted pregnancy and for adequate spacing between two pregnancies. There are many socio demographic and cultural factors that influence the choice of contraception in rural community in India. Third trimester of pregnancy is ideal time for counselling the women regarding breast feeding and contraception. The objective of the present study was to find out the choice of postpartum contraception among antenatal women and the socio demographic and cultural determinants that influence this choice. Methods: Six hundred pregnant women were interviewed regarding their choice of postpartum contraception during their antenatal visit in third trimester of pregnancy, using a pre-validated and pre-tested brief questionnaire. The choices were compiled and analysed to draw conclusions. Results: Postpartum sterilization was choice of 30% of multiparous women. Primi-parous women either opted for barrier contraception like condom (10%), intrauterine contraception (9%) or oral steroidal pills (8%). The progesterone injectable contraceptives and centchroman each were chosen by 2% respondents. There was strong influence of education, parity, sex of the living children on the choice of contraception. It was observed that 40% of women did not want to use hormonal pills and intrauterine contraceptives due to strong age old misbelieves associated with them. Conclusions: Women in rural area prefer permanent method of contraception in the form of tubectomy operation after having desired number of children. There is insufficient spacing between pregnancies due to either non-use of contraception or inconsistent use of temporary method of contraception. More than 50% women are dependent on the husband regarding the choice and practice of contraception. The level of education of woman, age at marriage, socio economic class, desired sex combination of children are strong determinants of choice of contraception.